The South China Sea Disputes : Makings of a New Cold War? - Teo, KB (2018)
Tensions in the South China Sea (SCS) have somewhat abated but the latent flashpoint remains. In mid-October 2018, a near collision took place between an American and Chinese warship. The US has attacked Beijing’s expansionism. In September 2018, Japan conducted its first-ever submarine drills in the waters. If the dispute escalates, ASEAN will not be able to avoid the negative fallout.